2017
DOI: 10.1108/jsbed-01-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education knowledge transfer in a conflict Sub-Saharan African context

Abstract: Purpose The purpose of this paper is to explore how entrepreneurship education (EE) interacts with knowledge transfer and entrepreneurial behaviour in a conflict Sub-Saharan African context. Design/methodology/approach In-depth telephone interviews of 20 participants who benefited from EE knowledge transfer were used to document and analyse the effect of EE on their behaviours as micro-entrepreneurs in a conflict zone. Findings These participants exhibited rare forms of innovative behaviour, through their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 82 publications
0
18
0
3
Order By: Relevance
“…New business creation promotes economic growth in both developed and emerging economies (Amezcua et al, 2013). Entrepreneurship holds promise as an engine of economic growth especially in sub-Saharan Africa (Anosike, 2018). In the case of agribusinesses in developing countries, entrepreneurship may assure food security as well.…”
Section: Introductionmentioning
confidence: 99%
“…New business creation promotes economic growth in both developed and emerging economies (Amezcua et al, 2013). Entrepreneurship holds promise as an engine of economic growth especially in sub-Saharan Africa (Anosike, 2018). In the case of agribusinesses in developing countries, entrepreneurship may assure food security as well.…”
Section: Introductionmentioning
confidence: 99%
“…Many Nigerians do not actually believe that entrepreneurship is a viable career alternative after graduation (Kolade, 2018;Lawal et al, 2018;Ndagi, 2018). This explanation is further strengthened by the fact that Nigeria lacks the conducive environment to actually foster the creation and growth of entrepreneurial ventures (Ezeagba, 2017;Oladimeji, Eze, & Akani., 2018;Okon, 2018): electricity is epileptic at best (Kolawole et al, 2019;Olowosejeje, Leahi, & Morrison, 2019;Samuel & Ayeni, 2019); the road networks are exceedingly poor and littered with pot-holes (Chakamera & Alagidede, 2018;Iyanda et al, 2018;Olowogbon et al, 2019); pipe-borne water is a luxury (Abubakar, 2018;Ogbuabor & Onwujekwe, 2018;Simukonda et al, 2018); new ventures are plagued with multiple taxes from various government agencies (Ede, 2018;Asongu & Odhiambo, 2019;Okpala et al, 2019); access to crucial start-up capital is extremely limited for new ventures (Anosike, 2018;Hansen et al, 2018;Oladimeji & Aina, 2018), and Nigerians do not trust in locally-made products, preferring to purchase imported goods which they perceive as been of higher quality due to stringent quality control standards present in these countries that are absent in Nigeria (Vadakepat, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on evidence access mechanisms and combined approaches to KE [91] at preparedness [93] and recovery stages [92]. Theoretical frameworks underpinning KE were PLOS ONE not described.…”
Section: Terror Related Crisesmentioning
confidence: 99%